Študentski domovi - humani način bivanja študentov - Seljak, Igor (Urbani izziv, 2000)
With the increasing number of students at the University of Ljubljana (Slovenia), the shortage of students accomodation in students halls has increased. Alongside the necessity for building new accomodation capacities an opportunity has emerged for the enforcement of new living standards, that should replace outdated guidelines from the sixties. During the preparation of the project we analysed all the important elements of students accomodationin students halls. Analyses of the present conditions in existing halls were performed, including positive and negative elements. We also conducted a comparative research of students halls in various European countries. In conclusion a list of recommendations with real guidelines was prepared, that could be ussed by investors when proposing new development of such buildings, as well as architects and planners.
Keywords: architecture; arhitektura; kvaliteta; Slovenia; Slovenija; stanovanjska gradnja; študentski domovi